Who is happy? Who is not? Cellular-phone mediated communication among Filipina domestic workers in Hong Kong (Silliman Journal, 2008)
One hundred fifty seven Filipina domestic workers in Hong Kong participated in an investigation into cellular phone use as a medium of communication and as an instrument to levels of happiness. Majority were middle-aged, college graduates, married, Roman Catholic and were into 6-10 years in their current jobs. Through interview and survey, the participants expressed feeling happy owning a cellular phone, which is associated with a certain level of life satisfaction. However, statistical findings showed that this did not significantly relate to their over-all high level of happiness. It was also found that there was a positive relationship between the extent to which calling was able to create positive relationships and facilitate disclosure of information about oneself and one's happiness. The same was true with texting except between calling and facilitating disclosure about oneself. In both calling and texting, maintaining relationships was negatively related with happiness. Although participants believed that calling and texting could maintain rather than create relationships or aid in the disclosure of information about oneself, it was not found to significantly affect their level of happiness.